Non-Stereotypical Female Librarians in the Library Wars Film - Dyah Paramaratri; Luki Wijayanti (Program Studi Ilmu Perpustakaan UIN Alauddin, 2021)
This research discusses non-stereotypical female librarian in The Library Wars movie. This research will examine the scenes on which features non-stereotypical female librarian and their interactions with their daily work environment. This study uses a descriptive qualitative method based on a visual representation analysis framework of social actors where the framework shows distance, relation, and interaction between social actors represented by the audience. The results of this study indicated that female librarian was indeed portrayed as non-stereotypical figures who were close to military training. The female librarian is described as a library guard who is a smart person, determined to defend what she thinks is right, and has the courage to take a stand on what she believes. Even so, female librarians are still portrayed as weak figures and female librarians are sometimes portrayed as frivolous and arrogant.